Analisis Pengaruh Inflasi Dan Risiko Sistemik Terhadap Stabilitas Keuangan Perbankan Di Indonesia Melalui Suku Bunga Sebagai Variabel Mediasi - Ismail, Kaifa; Afandy, Chairil; Nurazi, Ridwan (Jambura Economic Education Journal, 2026)
Maintaining the stability of the banking industry's finances is a critical component of ensuring the resilience of the financial system and promoting long-term economic expansion. Through interest rates as a mediating factor, this research seeks to examine the effects of inflation and systemic risk on the financial stability of Indonesian banking. The research employs a quantitative methodology using secondary data gathered from the Financial Services Authority, Bank Indonesia, and the Indonesia Stock Exchange between 2020 and 2024. Purposive sampling was used to choose the 20 banking firms that made up the study sample. Multiple linear regression and the Sobel test for mediation were the analytical methods used. The findings indicate that systemic risk has a considerable impact on financial stability, but inflation does not. Interest rates are also impacted by inflation and systemic risk, which in turn have a big impact on financial stability. The findings of this research offer implications for banking and monetary regulators as they create systemic risk management policies aimed at preserving the financial stability of Indonesia's banking industry.